Gambaran Coping Stress pada Mahasiswa Semester Akhir di Universitas Negeri Malang - Galuh Octa Rastika; Sabrina Qaanitah Putri; Dedi Setiawan; Dewi Fatmasari Edy (Flourishing Journal, 2024)
Stress is a reaction of the body to respond to a situation considered a threat. A person who experiences stress often faces burdens that are too heavy or beyond individual capacity, such as physical demands, the environment, and social situations beyond one's control. The aim of this research is to determine the description of stress coping applied by final-year students at the State University of Malang in dealing with pressure or other problems they are facing during the final semester. This research is in the form of descriptive qualitative research with a case study research model related to stress-coping mechanisms applied by final-year students at the State University of Malang. In collecting data, researchers conducted in-depth informant interviews with students in semester 7 and above studying at the State University of Malang. Next, the interview results will be stated verbatim, analyzed thematically, and interpreted descriptively. The participants used in this research were four final year students at the State University of Malang from various faculties. After conducting an analysis based on participants' answers, the results showed that there were several ways for participants to deal with stress, including decision-making, courage to take risks, responsibility, coping, and survival. AbstrakStres merupakan suatu reaksi tubuh untuk merespon keadaan yang dianggap ancaman. Seseorang yang mengalami stres seringkali menghadapi beban yang terlalu berat atau yang diluar kapasitas individu, seperti tuntutan fisik, lingkungan, dan situasi sosial yang diluar kendali seseorang. Tujuan dari penelitian ini adalah untuk mengetahui gambaran coping stress yang diterapkan oleh mahasiswa tingkat akhir di Universitas Negeri Malang dalam menghadapi tekanan atau problematika lain yang tengah dihadapi selama semester akhir. Penelitian ini berbentuk kualitatif deskriptif dengan model penelitian studi kasus berkaitan dengan mekanisme coping stress yang diterapkan oleh mahasiswa tingkat akhir di Universitas Negeri Malang. Dalam mengumpulkan data, peneliti melakukan in-depth interview informan kepada mahasiswa semester 7 keatas yang berkuliah di Universitas Negeri Malang. Selanjutnya, hasil dari wawancara tersebut akan dituang dalam verbatim dan dianalisis dengan cara tematik serta diinterpretasikan secara deskriptif. Partisipan yang digunakan dalam penelitian ini adalah empat mahasiswa tingkat akhir Universitas Negeri Malang dengan berbagai fakultas. Setelah dilakukan analisis berdasarkan jawaban pasrtisipan, didapatkan hasil bahwa terdapat beberapa cara dari partisipan dalam menghadapi stres, diantaranya yakni: pengambilan keputusan, berani mengambil resiko, bertanggung jawab, coping, dan usaha bertahan.